Author Correction: All organic nanomedicine for PDT-PTT combination therapy of cancer cells in hypoxia (vol 14, 17507, 2024) - Urazaliyeva, Anel; Kanabekova, Perizat; Beisenbayev, Almaz; Kulsharova, Gulsim; Atabaev, Timur; Kim, Sehoon; Lim, Chang-Keun (Nature Publishing Group, 2024)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-024-68077-4, published online 30 July 2024 The original version of this Article contained an error in the Acknowledgements section. The name of the Funding source was incorrect: “This work was supported by the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP14870133) and Nazarbayev University (Grant Nos. 021220FD0151 and 11022021CRP1501). ChatGPT edited the English grammatical errors.” now reads: “This research has been funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AP14870133) and Nazarbayev University (Grant Nos. 021220FD0151 and 11022021CRP1501). ChatGPT edited the English grammatical errors.”